Feasibility and greenhouse gas emissions of timber structures in solar photovoltaic carport construction - Ranta, Samuli; Akulenko, Elena; Huerta, Hugo; Wang, Shuo; Jouttijärvi, Sami; Miettunen, Kati (Frontiers in Built Environment, 2024)
This contribution focuses on reducing the greenhouse gas (GHG) emissions of solar photovoltaic (PV) carport structures by replacing carbon-intensive steel with a wood-based material. There is a growing need for PV systems that are suitable for urban environments where the lack of roof spaces and open land limits the use of traditional PV installations. To date, PV carports have been mainly constructed with steel, which has a high carbon footprint and can be considered aesthetically unattractive. Wood structures, on the other hand, could act as carbon storage and thus reduce the GHG emissions of the whole system. Emissions and costs of supporting structures for PV systems have received very little attention, and there is virtually no literature specific to them. This study compares wood-based glued laminated timber (GLT) structures with conventional steel structures by investigating the GHG emissions and economic feasibility. The simulated 485 kWp system with wooden structures yielded base-case lifetime GHG emissions of 11.3 g CO2 eq / kWh in Turku Finland (60°N), and 8.2g CO2 eq/ kWh in Dijon France (47° N), representing a 48% lower value compared to systems with steel structures. Furthermore, wooden structures were competitive in terms of costs, being approximately 25 % cheaper. Thus, wooden structures provide a very attractive way to make infrastructure integrated PV more sustainable.